Characterisation of off-flavour compounds and their sensory impact on Lupinus angustifolius L.: Special emphasis on volatile markers of green, grassy, and beany aroma notes and bitter taste - Piyumi Chathurangi Wanniarachchi; Russell S.J. Keast; Simone Lewin; Gregory R. Cawthray; Rewati Raman Bhattarai; Mauro Mocerino; Sarita Jane Bennett; Greg Shea; Ranil Coorey (Food Chemistry, 2026)

A roadmap for the conservation of freshwater mussels in Europe - Ronaldo Sousa; Tadeusz Zając; Dariusz Halabowski; Olga V. Aksenova; Yulia V. Bespalaya; Francisco Carvalho; Paulo Castro; Karel Douda; Janine P. da Silva; Noé Ferreira‐Rodríguez; Juergen Geist; Clemens Gumpinger; et al. (Conservation Biology, 2023)
Europe has a long history of human pressure on freshwater ecosystems. As pressure continues to grow and new threats emerge, there is an urgent need for conservation of freshwater biodiversity and its ecosystem services. However, whilst some taxonomic groups, mainly vertebrates, have received a disproportionate amount of attention and funds, other groups remain largely off the public and scientific radar. Freshwater mussels (Bivalvia, Unionida) are an alarming example of this conservation bias and here we point out six conceptual areas that need immediate and long‐term attention: knowledge, threats, socioeconomics, conservation, governance and education. The proposed roadmap aims to advance research, policy and education by identifying the most pressing priorities for the short‐ and long‐term conservation of freshwater mussels across Europe.

The role of anthropogenic habitats in freshwater mussel conservation - Ronaldo Sousa; Dariusz Halabowski; Anna M. Labecka; Karel Douda; Olga Aksenova; Yulia Bespalaya; Ivan Bolotov; Juergen Geist; Hugh A. Jones; Ekaterina Konopleva; Michael W. Klunzinger; Carlos A. Lasso; et al. (Global Change Biology, 2021)
Anthropogenic freshwater habitats may provide undervalued prospects for long‐term conservation as part of species conservation planning. This fundamental, but overlooked, issue requires attention considering the pace that humans have been altering natural freshwater ecosystems and the accelerated levels of biodiversity decline in recent decades. We compiled 709 records of freshwater mussels (Bivalvia, Unionida) inhabiting a broad variety of anthropogenic habitat types (from small ponds to large reservoirs and canals) and reviewed their importance as refuges for this faunal group. Most records came from Europe and North America, with a clear dominance of canals and reservoirs. The dataset covered 228 species, including 34 threatened species on the IUCN Red List. We discuss the conservation importance and provide guidance on how these anthropogenic habitats could be managed to provide optimal conservation value to freshwater mussels. This review also shows that some of these habitats may function as ecological traps owing to conflicting management practices or because they act as a sink for some populations. Therefore, anthropogenic habitats should not be seen as a panacea to resolve conservation problems. More information is necessary to better understand the trade‐offs between human use and the conservation of freshwater mussels (and other biota) within anthropogenic habitats, given the low number of quantitative studies and the strong biogeographic knowledge bias that persists.